Dental Phobia among Pregnant Women: Considerations for Healthcare Professionals. (10th April 2020) - Nazir, Muhammad; Alhareky, Muhanad
Abstract : Objective . To report the prevalence of dental phobia and associated factors among pregnant women. Materials and Methods . This cross-sectional study included pregnant women visiting hospitals in Dhahran, Khobar, and Dammam in Saudi Arabia. The Modified Dental Anxiety Scale (MDAS) was used to assess dental anxiety and phobia. The score of MDAS ranges from 5 to 25, and a cutoff value of 19 was used to identify participants with dental phobia. Results . The study analyzed data of 825 participants with mean age of 29.08 ± 5.18 years. The prevalence of dental phobia was 16.1%. About 46.9% of the sample believed that dental treatment should be avoided during pregnancy, and the importance of regular dental checkup was recognized by 16.4% of the participants. Dental phobia was associated with the perception of the health of teeth (P 0.004) and gums (P 0.016). Multiple logistic regression showed that being under the age of 30 years (OR 0.63, P 0.019) and updating knowledge about oral health (OR 0.49, P 0.006) were significantly associated with reduced likelihood of dental phobia. However, having bad dental experience (OR 2.13, P 0.001) and being in first trimester of pregnancy (OR 1.57, P 0.033) were significantly associated with increased odds of dental phobia. Conclusions . A considerable proportion of pregnant women reported dental phobia. The bad dental experience was associated with increased dental phobia. However, reduced likelihood of dental phobia was associated with updating oral health knowledge. Healthcare professionals may consider these factors to reduce dental phobia and improve oral health of pregnant women.